Clima organizacional en empresas del sector hidrocarburos: el papel del propósito corporativo y el compromiso laboral - Alcaraz Altamirano, María de Lourdes (Universidad Michoacana de San Nicolas de Hidalgo, 2025)
This research aimed to analyze the influence of organizational purpose and work commitment on the organizational climate of a company in the hydrocarbon sector dedicated to the sale and distribution of LP gas. The study employed an exploratory, descriptive, and correlational design with a quantitative approach. The sample consisted of 205 employees, selected from a total population of 422, to whom a structured questionnaire was applied, comprising 26 items related to the study variables and 8 sociodemographic questions. Data analysis was conducted using the Spearman’s Rho correlation test, since the assumptions of normality were not met. The results showed a strong and positive relationship among the variables: between organizational climate and organizational purpose (ρ = .868), between organizational climate and work commitment (ρ = .698), and between purpose and commitment (ρ = .783). It is concluded that strengthening the organizational climate depends on the proper development of the organizational purpose and the work commitment.

Esta investigación tuvo como objetivo Analizar la influencia del propósito organizacional y el compromiso laboral en el clima organizacional de una empresa del sector hidrocarburos dedicada a la venta y distribución de Gas L.P. El diseño de la investigación exploratorio, descriptivo y correlacional, con un enfoque cuantitativo. La muestra estuvo conformada por 205 empleados seleccionados de una población total de 422 a los cuales se les aplicó un cuestionario estructurado con 26 ítems relacionados con las variables de estudio y 8 preguntas sociodemográficas. El análisis se realizó la prueba Rho de Spearman al no cumplirse los supuestos de normalidad- Los resultaros mostraron la relación fuerte y positiva entres las variables: entre clima organizacional y propósito corporativo (ρ = ,868), entre clima organizacional y compromiso laboral (ρ = ,698), y entre propósito y compromiso (ρ = ,783). Se concluye que para fortalecer el clima organizacional depende del buen desarrollo del propósito organizacional y compromiso laboral.
Facultad de Contaduría y Ciencias Administrativas. Maestría en Administración
Keywords: info:eu-repo/classification/cti/5; FCCA-M-2025-1757; Clima organizacional; Propósito corporativo; Compromiso laboral; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/19516